The complete mitochondrial genome of the freshwater crab Potamiscus motuoensis (Decapoda: Brachyura: Potamoidea) - Wang, Songbo (Mitochondrial DNA B Resour, 2020)
Potamiscus motuoensis is the only one freshwater crab species distributed in Yarlung Zangbo River Grand Canyon and its complete mitochondrial genome was obtained for the first time. The complete mitochondrial genome of P. motuoensis is 17,971 bp in length, including 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and 1 control region. In addition, the mitogenome has 19 noncoding regions ranging from 1 to 1396 bp in length. The report of the mitochondrial genome will enrich the species diversity of Yarlung Zangbo River Grand Canyon and provide data support for further research.